2020
DOI: 10.3390/en13195005
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Check-List Strategy to Evaluate the Potential of Operational Improvements in Wastewater Treatment Plants

Abstract: With increasing demands for cleaning and purification of water, wastewater treatment plants (WWTP) require their most efficient operation. The operators are thus obliged to constantly review the efficiency of the processing units and technological equipment of WWTPs and seek opportunities for improvements. To increase the efficiency of particular equipment, the important parameters to be used for the intensification must be correctly selected. A common WWTP consists of different types of processing units, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…In the case of the water industry, water demand is expected to double by 2035 [2]; therefore, large amounts of additional energy are expected to be consumed for water supply and wastewater treatment, unless the energy efficiency of plants is increased. Wastewater treatment plants (WWTP) have been found to have considerable potential for reducing energy consumption and costs [3]- [5], and several strategies for the energyefficient operation of WWTPs are being introduced [6]. The main energy-intensive tasks in a WWTP include pumping and aeration processes.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of the water industry, water demand is expected to double by 2035 [2]; therefore, large amounts of additional energy are expected to be consumed for water supply and wastewater treatment, unless the energy efficiency of plants is increased. Wastewater treatment plants (WWTP) have been found to have considerable potential for reducing energy consumption and costs [3]- [5], and several strategies for the energyefficient operation of WWTPs are being introduced [6]. The main energy-intensive tasks in a WWTP include pumping and aeration processes.…”
Section: Introductionmentioning
confidence: 99%
“…One of the industrial sectors where this tendency is observed corresponds to the Wastewater Treatment Plants (WWTPs), which are characterised by running very complex processes where individual operations and actions can change the whole operation of the plant [ 7 ]. For that reason, a huge number of control loops are required in order to ensure that each individual operation is correctly performed.…”
Section: Introductionmentioning
confidence: 99%